(untitled) (Scientific journal of the Fergana State University, 2026)
This study scientifically substantiates the criteria for the formation and optimization of ecological networks based on MSPA and MCR models. The MSPA model, through morphological analysis of landscape structure, allows the identification of ecological cores, corridors, and isolated fragments, while the MCR model serves to assess ecological connectivity by considering various anthropogenic and natural resistance factors through the principle of minimum cumulative resistance. Furthermore, the possibilities of applying MSPA–MCR models to determine the optimal placement of ecological corridors and to ensure the integrity of natural landscapes have been analyzed. On this basis, opportunities for effective planning of ecological network elements, biodiversity conservation, and ensuring regional sustainable development have been considered.